THE COMMUNICATIVE-PRAGMATIC NATURE OF EVALUATION IN DISCOURSE - Sherzod Rabbimkulovich Yuldashev (Western European Studies, 2026)
This article examines the communicative-pragmatic relation between speech and the category of evaluation. The study applies discourse-pragmatic analysis, contextual interpretation, and a comparative approach. The findings show that evaluation functions as a pragmatic layer added to propositional content and generates social meaning through strategies, presuppositions, and implicatures, clarifying evaluation’s role in interaction.
Keywords: pragmatics; evaluation category; speech act